Awakening the Leviathan through Human Rights Law – How Human Rights Bodies Trigger the Application of Criminal Law - Pinto, Mattia (Utrecht Journal of International and European Law, 2018)
This article analyses the role that human rights bodies play in triggering the application of criminal law. By examining the jurisprudence of the Inter-American Court of Human Rights, the European Court of Human Rights, the UN Human Rights Committee, as well as other human rights bodies, the article discusses how these institutions have started imposing on states positive obligations to criminalise, prosecute and punish serious human rights violations. While criminal law has traditionally been seen as a threat to fundamental rights, human rights bodies have contributed to presenting criminal law in a positive vein, as an essential instrument of human rights protection. The mainstream of the human rights movement has largely lauded the trend. This article challenges this view, by presenting the pitfalls of using human rights law to extend the reach of criminal justice in order to ensure that perpetrators are held accountable. Not only the imposition of duties to criminalise and punish ends up restricting the accused’s fundamental rights and neglecting the conceptualisation of criminal law as ultima ratio, but the invocation of criminal-law enforcement might also contribute to enhancing the coercive power of the state and, therefore, make state abuses more likely.